2011
DOI: 10.1093/brain/awr098
|View full text |Cite
|
Sign up to set email alerts
|

Motor system hyperconnectivity in juvenile myoclonic epilepsy: a cognitive functional magnetic resonance imaging study

Abstract: Juvenile myoclonic epilepsy is the most frequent idiopathic generalized epilepsy syndrome. It is characterized by predominant myoclonic jerks of upper limbs, often provoked by cognitive activities, and typically responsive to treatment with sodium valproate. Neurophysiological, neuropsychological and imaging studies in juvenile myoclonic epilepsy have consistently pointed towards subtle abnormalities in the medial frontal lobes. Using functional magnetic resonance imaging with an executive frontal lobe paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
189
2
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(221 citation statements)
references
References 36 publications
22
189
2
8
Order By: Relevance
“…These areas connect to cingulate, caudate, putamen, frontal cortex, supplementary motor area, postcentral cortex, and occipital cortex,41 all cortical areas that are associated with GGE 36, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…These areas connect to cingulate, caudate, putamen, frontal cortex, supplementary motor area, postcentral cortex, and occipital cortex,41 all cortical areas that are associated with GGE 36, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…In an fMRI study using an executive frontal lobe paradigm, patients with juvenile myoclonic epilepsy showed increased functional connectivity between the motor system and the frontoparietal cognitive networks, providing an explanation for how cognitive effects can cause myoclonic jerks in juvenile myoclonic epilepsy. 24 It was suggested that the SMA, as a connector linking prefrontal cognitive areas and the motor system, may facilitate the occurrence of generalized seizures, a notion supported by alterations in anatomic connectivity of the SMA in juvenile myoclonic epilepsy. 25 To estimate the corticothalamic connectivity in juvenile myoclonic epilepsy, we parcellated the thalamus into several nuclei connected to different cortices by using probabilistic tractography.…”
Section: -24mentioning
confidence: 99%
“…Abb. 2e, f; [17]), die mit einer mittels DTI nachgewiesenen ebenfalls erhöhten strukturellen Konnektivität korrelierte [18]. Diese Befunde boten eine schlüssige Erklärung für das JMEspezifische Phänomen der Praxisinduktion, bei der eine Kombination aus kognitiver und manueller Tätigkeit motorische Anfälle triggern kann (über eine pathologische Hyperkonnektivität zwischen ansonsten getrennten funktionellen Systemen; .…”
Section: Funktionelle Mrt-befunde Bei Der Jmeunclassified
“…Diese Befunde bieten eine Erklärung für die typische Anfallstriggerung durch Praxisinduktion bei der JME. Ähnliche Befunde bei gesunden Geschwistern sprechen dafür, dass dieses fMRT-Merkmal erblich ist und somit als Endophä-notyp dienen kann ( [17,19], L links, R rechts) …”
Section: Zeitschrift Für Epileptologie 2 · 2018 145unclassified